2019
DOI: 10.1002/humu.23879
|View full text |Cite
|
Sign up to set email alerts
|

Alagille syndrome mutation update: Comprehensive overview ofJAG1andNOTCH2mutation frequencies and insight into missense variant classification

Abstract: Alagille syndrome is an autosomal dominant disease with a known molecular etiology of dysfunctional Notch signaling caused primarily by pathogenic variants in JAGGED1 (JAG1), but also by variants in NOTCH2. The majority of JAG1 variants result in loss of function, however disease has also been attributed to lesser understood missense variants. Conversely, the majority of NOTCH2 variants are missense, though fewer of these variants have been described. In addition, there is a small group of patients with a clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 86 publications
(115 reference statements)
3
132
1
5
Order By: Relevance
“…Previous studies have shown that these three testing strategies are capable of detecting up to~97% of pathogenic variants in ALGS. 5,6 Genome sequencing DNA was extracted from either whole blood or lymphoblastoid cell lines using the DNeasy Blood and Tissue Kit (Qiagen, Hilden, Germany). Short-read (2 × 150 bp) Illumina (Illumina, San Diego, CA) GS was performed at the Broad Institute Genomic Services (Boston, MA) using a PCR-free protocol at a targeted mean sequencing depth of 30×.…”
Section: Standard-of-care Testingmentioning
confidence: 99%
“…Previous studies have shown that these three testing strategies are capable of detecting up to~97% of pathogenic variants in ALGS. 5,6 Genome sequencing DNA was extracted from either whole blood or lymphoblastoid cell lines using the DNeasy Blood and Tissue Kit (Qiagen, Hilden, Germany). Short-read (2 × 150 bp) Illumina (Illumina, San Diego, CA) GS was performed at the Broad Institute Genomic Services (Boston, MA) using a PCR-free protocol at a targeted mean sequencing depth of 30×.…”
Section: Standard-of-care Testingmentioning
confidence: 99%
“…Cysteine loss within the JAG1 protein frequently results in missense mutations in ALGS patients [10], likely due to the unique type of bonds (disulfide bonds) that cysteine forms. Disulfide bridges between cysteine molecules are crucial for the stability of the tertiary and quaternary structures of proteins and hence, for their function.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented case, we identified a previously unknown missense variant – c.587G > A – within exon 4 of the JAG1 gene, which results in an amino acid alteration (p.Cys196Tyr) in the DSL domain of JAG1 that is responsible for its binding to the Notch2 receptor [ 10 ]. Exon 4 is the second most frequent location of pathogenic variants within the JAG1 gene [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 First described in 1969, AGS is estimated to affect 1:30 000–50 000 live births. 5 Its pathogenesis is related to mutations in JAG1 or NOTCH2 genes 1 that are expressed in fetal liver, lungs, brain, and kidneys, as well as adult heart, lung, skeletal muscle, and kidneys. AGS is most commonly associated with paucity of intrahepatic bile ducts that may lead to chronic cholestasis, as well as cardiac (pulmonary stenosis), ocular, and skeletal abnormalities (characteristic facial features).…”
Section: Discussionmentioning
confidence: 99%